EFEKTIVITAS MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA POST OPERASI - Faizal, Kgs Muhammad; Mulya, Mulya (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Today a number of diseases indicate an indication for surgery. After surgery, the patient will experience a weak condition and it will be difficult to carry out activities due to surgical procedures and surgical wounds that require time in the healing process. Data on general surgery in 2018 were 445 patients with a stay of 3-5 days Nursing interventions that can be performed by postoperative patients are early mobilization. Early mobilization includes factors that can affect the surgical wound healing process. The purpose of this study was to determine the effectiveness of early mobilization on post operative wound healing. The design of this study was quasi-experimental with a post-test only control group design. The population was all postoperative patients at the Depati Hamzah Regional Hospital in Pangkalpinang City. The sampling technique uses non random sampling by accidental sampling, with 12 respondents in the intervention group and 12 respondents in the control group. The test used is the T test of two different dependent means. The results of the study were that there was a significant difference between wound healing performed early mobilization and healing which was not carried out early mobilization with a p value: 0.002. The suggestion from this research is that a hospital can implement early mobilization after 6 hours postoperatively, so that the wound healing time will be faster.